Estimate of the subglacier dielectric constant of an ice shelf using a ground-penetrating step-frequency radar - Hamran, Svein Erik; Erlingsson, Bjørn; Gjessing, Yngvar; Mo, Per (IEEE Transactions on Geoscience and Remote Sensing, 1998)
The mass balance of the Antarctic ice cap, its stability, and the role of the surrounding ice shelf in bottomwater mass formation is, to a large extent, dictated by processes associated with subsurface freezing and melting, where the submerged ice meets the surrounding ocean. It is demonstrated how multifrequency ground-penetrating radar data collected at the Riiser-Larsenisen can be used to examine the physical conditions of the ice-shelf subsurface. The received radar signal from three different frequency intervals, 10-30, 155-170, and 330-360 MHz (range of wavelengths from 15 to 0.5 m in the ice), was analyzed by using a plane reflector model. It is demonstrated that the data can be successfully used to distinguish between types of ice at the ice-ocean interface, such as for freezing marine ice, melting marine ice, melting meteoric ice from the ice cap, and melting firn/ice. The data analysis shows that the subsurface can be regarded as rough on length scales in the order of 1 m.
Keywords: Antarktis; brehylle; fjernanalyse; geofysikk; georadar; glasiologi; isbreer; isbrem; isshelf; oseanografi

Moorings from the Filchner Trough and the Ronne Ice Shelf front: preliminary results - Woodgate, Rebecca A; Schröder, Michael; Østerhus, Svein (Filchner-Ronne Ice Shelf Programme. Report, 1998)
Keywords: Sørishavet; oseanografi

Formation and circulation of Ice Shelf Water in the Weddell and Ross seas - Nøst, Ole Anders (University of Bergen, 1995)
Publication Title: Geophysical Institute, Oceanography, University of Bergen
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Water mass distribution and tides along the Filchner-Ronne ice shelf: preleminary [sic] results from the Norwegian Antarctic Expedition 1992/93 - Gammelsrød, Tor (Filchner-Ronne Ice Shelf Programme. Report, 1994)
Keywords: Sørishavet; oseanografi

Distribution of Water Masses on the Continental Shelf in the Southern Weddell Sea - Gammelsrød, Tor; Foldvik, Arne; Nøst, Ole Anders; Foldvik, Ø.; Anderson, Leif G.; Fogelqvist, Elisabet; Olsson, K. Anders; Tanhua, Toste; Jones, Elizabeth Peter; Østerhus, Svein (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
Water properties on the continental shelf in the southern Weddell Sea observed during NARP 92/93 are presented. The station distribution includes a section close to the floating ice shelf from the Filchner Depression to the Antarctic Peninsula. Temperature, salinity, oxygen, silicate, CFC-ll and CFC-12 distributions are shown. Melting under the ice shelves, circulation systems, residence times, sediment/water interactions and bottom water formation are discussed. Ice Shelf Water (ISW), which is formed by cooling and melting below the floating ice shelf, seems to be about 10 years older than its parent water mass, which indicates the residence time below the ice shelf. The average melting rate below the Filchner Ronne ice shelf, based on the volume flux of ISW in the Filchner Depression is estimated to be 0.1 m/year. Compared with earlier observations considerable changes were found in the water characteristics and distribution: The temperature of the Weddell Deep Water has increased 0.7°C since 1977. Western Shelf Water, usually dominating the bottom layers in the Filchner Depression and on the Berkner Shelf, was found only in the Ronne Depression.
Keywords: NARP 1992/93; Sørishavet; Weddellhavet; geofysikk; oseanografi

Bunnvannsstrømmer på kontinentalskråningen i Weddellhavet - Nordlund, Nina (Universitetet i Bergen, 1992)
Publication Title: Geofysisk institutt. Universitetet i Bergen
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; havstrømmer; oseanografi

En modell for sirkulasjonen under isshelfene i Weddelhavet og Rosshavet - Nøst, Ole Anders (O. A. Nøst, 1992)
Publication Title: [Geophysical Institute, Oceanography, University of Bergen]
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

Glaciologic and oceanographic studies on Fimbulisen during NARE 1989/90 - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1990)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; glasiologi; isbrem; oseanografi

Oceanographic research during NARE-84/85 - Foldvik, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1986)
Keywords: Sørishavet; oseanografi

Alternate Carbon Pathways at Lower Trophic Levels in the Antarctic Food Web - Hewes, Christopher D; Holm-Hansen, Osmund; Sakshaug, Egil (Antarctic Nutrient Cycles and Food Webs, 1985)
Keywords: Sørishavet; Weddellhavet; diatomeer; fytoplankton; krill; marin biologi; oseanografi; plankton

Sea bed feauters in the Blåenga area, Weddell Sea, Antarctica - Lien, Reidar (Université Laval, 1981)
Pages: 706-716 Publication Title: POAC 81 : The Sixth International Conference on Port and Ocean Engineering under Arctic Conditions Volume: 2 Place: Quebec, Canada
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; geologi; havbunnen; kongress; oseanografi; symposium

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and icebergs - Gade, Herman G. (Journal of Physical Oceanography, 1979)
Steady-state conditions are assumed to exist everywhere in the case of melting of the underside of an infinite slab of ice floating in sea water. Basic transfer equations for heat and salt are established and solutions derived for the interior corresponding to given far field values of the temperature and salinity of the water. The solutions are discussed in the T-S diagram where the behavior is particularly simple. Determining parameters are the characteristic velocities ks/d and Ks/h, where ks and Ks are the molecular and turbulent diffusivities, respectively, of salt, d and h the thicknesses of the corresponding laminar and turbulent layers. Also the nonmelting/nonfreezing case is discussed and the determining parameter established. Application of the theory to the Ross Ice Shelf (Little America V) gives acceptable results with d = 2 × 10−3 m and Ks = 20 −30 × 10−4 m2 s−1. Analysis of the static stability of the melt water mixtures reveals that with ambient temperatures approaching 17°C, the stratification becomes unstable. Icebergs brought to tropical waters will cause melt water mixtures to intrude at subsurface levels. Finally, convection obtained in laboratory experiments with melting ice in sea water is reported to be in concordance with the theoretically derived stability criterion.
Keywords: Sørishavet; geofysikk; glasiologi; hydrologi; oseanografi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Pages: 75-82 Publication Title: POAC 79 : The Fifth International Conference on Port and Ocean Engineering Under Arctic Conditions Volume: 3 Place: Trondheim, Norway
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

Bottom currents in the Weddel Sea. Results of long time curretmeter moorings at 74°S, 40°W, during IWSOE 1968-1973 - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1974)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; oseanografi

Thermohaline convection in the vicinity of an ice shelf - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1974)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: AABW; Sørishavet; bunnvannet; ekspedisjoner; havis; isshelf; oseanografi; sjøis; sjøvann

Theories of bottom water formation, recent investigations in the Weddell Sea and the effects of super cooling by the ice cap - Mosby, Håkon (Japan Society for the Promotion of Science, 1971)
Pages: 126-127 Publication Title: The Ocean world : proceedings of Joint Oceanographic Assembly, IAPSO, IABO, CMG, SCOR Place: Tokyo, Japan
Keywords: Sørishavet; Weddellhavet; bunnvannet; kongress; oseanografi; sjøvann

Cruise reports. International Weddell Sea Oceanographic Expedition : conducted onboard USCGC GLACIER (WAGB-4) - Kvinge, Thor (University of Bergen, 1970)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; geofysikk; oseanografi

International Weddell Sea oceanographic expedition : position and weather journal USCGC Glacier - Kvinge, Thor (University of Bergen, 1970)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Remarks on processes pertinent to the formation of bottom water in the Weddel Sea - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1969)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. A preliminary report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; oseanografi

IWSOE - 69 : position and weather journal USCGC "Glacier" - Kvinge, Thor (University of Bergen, 1969)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Technical report on project to measure currents related to the formation of Antarctic bottom water in the Weddell Sea : United States Antarctic Research Program : International Weddell Sea Oceanographic Expedition, 1968 : conducted onboard USCGC glacier (WAGB-4) - Kvinge, Thor (University of Bergen, 1968)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; ekspedisjoner; isberg; observasjoner; oseanografi; sjøvann

Bottom water formation - Mosby, Håkon (SCAR/SCOR/IAPO/IUBS, 1966)
Pages: 47-57 Publication Title: Symposium on Antarctic Oceanography Place: Santiago, Chile
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

South Atlantic bottom water - Mosby, Håkon (Scientific Committee on Antarctic Research, 1966)
Pages: 11-20 Publication Title: Symposium on Antarctic Ice and Water Masses Place: Tokyo, Japan
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Publisher: Norges jordskiftedommer- og landmålersamband Place: Oslo
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

Narrative of the Expedition - Larsen, Nils (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

The Norwegian Antarctic expedition in the "Brategg 1947-1948 - Mosby, Håkon (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

"Brategg"-ekspedisjonen = The "Brategg" expedition - Holgersen, Holger (Norsk hvalfangst-tidende, 1948)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ornitologi; oseanografi

Currents of the Antarctic Ocean - Sverdrup, Harald Ulrik (Oceanography for meteorologists : H.U. Sverdrup, 1942)
Keywords: Sørishavet; havstrømmer; meteorologi; oseanografi

Nomenclature of the submarine features of the southern seas - Mosby, Håkon (Report of the Committee on the Criteria and Nomenclature of the Major Divisions of the Ocean Bottom, 1939)
Keywords: Sørishavet; geofysikk; oseanografi; topografi

On vertical circulation in the ocean due to the action of the wind with application to conditions within the Antarctic circumpolar current - Sverdrup, Harald Ulrik (Discovery Reports, 1933)
Keywords: Sørishavet; ekspedisjoner; forskning; havstrømmer; oseanografi

Polaraaret 1932-1933 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; forskning; klima; meteorologi; oseanografi

On the conditions for the production of plankton in the sea - Gran, Haaken Hasberg (Conseil Perm. Internat. pour I'Explor. de la Mer. Rapp. et Proces-Verb., 1931)
Keywords: Sørishavet; Weddellhavet; krill; marin biologi; oseanografi; plankton; zooplankton

The "Norvegia" Antarctic expedition of 1929-1930 - Long, A T (The Hydrographic Review, 1931)
Keywords: Antarktis; Dronning Maud Land; Sørishavet; ekspedisjoner; geografi; kartlegging; logistikk; oseanografi

Litt om "Norveiga"-ekspedisjonen 1927-28 og dens arbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1929)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; forskning; geografi; marinbiologi; oseanografi

Die Eistrift im Weddelmeer - Sverdrup, Harald Ulrik (Annalen der Hydrographie und maritimen Meteorologie, 1928)
Keywords: Sørishavet; glasiologi; havis; oseanografi